Incidence of Antiresorptive Agent-Related Osteonecrosis of the Jaw in Urologic Cancers - Kawanishi, Hiroaki (Hinyokika kiyo. Acta urologica Japonica, 2022)
Antiresorptive agent-related osteonecrosis of the jaw (ARONJ) is a serious adverse event of bone resorption inhibitors (BRIs), such as zoledronic acid and denosumab. Based on the results of phase 3 clinical trials for BRIs, the frequency of ARONJ is 1 to 2%, but the actual frequency is presumed to be higher. We studied 143 patients with urologic cancers with bone metastases who were treated with zoledronic acid or denosumab at our hospital between April 2007 and March 2020. ARONJ occurred in 24 patients (16.8%) ; that is, 14 of the 113 patients (12.4%) who received zoledronic acid alone, 8 of the 24 patients (33.3%) who received denosumab alone, and 2 of the 6 patients (33.3%) who sequentially switched from zoledronic acid to denosumab. ARONJ was cured in 8 patients (33.3%), improved in 3 patients (12.5%), unchanged in 4 patients (16.7%), and worsened in 9 patients (37.5%). The frequency of ARONJ increased as the duration of BRI administration prolonged. Time-to-ARONJ was shorter in patients treated with denosumab than in patients treated with zoledronic acid. The occurrence of ARONJ may be underestimated; therefore, further studies are needed to investigate the actual frequency of ARONJ in Japan